Biosynthesis of silver nanoparticles using aqueous extract of Phyllanthus acidus L. fruits and characterization of its anti-inflammatory effect against H2O2 exposed rat peritoneal macrophages. (April 2017) - Manikandan, R.; Beulaja, M.; Thiagarajan, R.; Palanisamy, S.; Goutham, G.; Koodalingam, A.; Prabhu, N.M.; Kannapiran, E.; Basu, M. Jothi; Arulvasu, C.; Arumugam, M.
Graphical abstract: Highlights: This is the first report of the green synthesis of AgNPs using Phyllanthus acidus. The synthesized AgNPs were characterized by UV–vis, SEM, EDX, XRD, FTIR and TEM. We assayed the anti-inflammatory potential of these AgNPs in rat peritoneal macrophages. Abstract: The green synthesis and characterization of silver nanoparticles (AgNPs) derived from plants impart ecological and economic benefits to AgNPs. In addition, AgNPs have potential therapeutic roles in cytoprotectivity and anti-inflammation. The present work utilizes the aqueous extract of Phyllanthus acidus fruits for the production of AgNPs from aqueous silver nitrate solution. The synthesized AgNPs were characterized spectrophotometrically Fourier transform infrared spectroscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy, scanning electron microscopy and transmission electron microscopy analysis. The characterized AgNPs showed potent anti-inflammatory activity by scavenging nitric oxide and superoxide anions. In addition, blunting of the expression of pro-inflammatory cytokine interleukin 1 beta (IL-1β) assayed both by ELISA and Western blot, using H2 O2 – induced inflammation in rat peritoneal macrophages. Furthermore, short-term exposure to P. acidus- mediated green-synthesized AgNPs did not affect the viability of peritoneal macrophages, as assessed by MTT assay. Our findings indicate that P. acidus- mediated green-synthesized AgNPs could be a potential therapeutics to treat inflammatory diseases.